Distal radius volar T plate versus distal clavicle pre-contoured locking plate in Neer 2b distal clavicle fracture; a randomized control trial study - Amir Mehrvar; Reza Zandi; Mohammad Ali Okhovatpour; Shahab Sarlak; Mohammadreza Minator Sajjadi; Akbar Ehsani; Ahmadreza Ahmadi Abdashti (Journal of Orthopedic and Spine Trauma, 2024)
Purpose The purpose of current study was to compare the clinical and radiographic outcomes of distal radius volar T plate and pre-contoured locking plate in distal clavicle fracture.